Morphological characters and karyology of Miogryllus piracicabensis Piza (Orthoptera : Gryllidae) - Mesa, A.; Garcia-Novo, P.; Roat, T.; Portugal, C. (Entomological Society Brasil, 2004)
The genus Miogryllus includes a considerable number of species, most of them still undescribed. From those already described, the amount of afforded details on morphology is not always enough to recognize the species, missing information on phallic and pars stridens structures as well as karyology. The present paper aims to improve these information, on the species M. piracicabensis.
Keywords: Gryllinae; phallic sclerites; par stridens; proventiculus structure; cytogenetics